Optical properties of 2D semiconductor WS2 - Cong, Chunxiao (2020)
2D semiconductor tungsten disulfide (WS2) attracts significant interest in both fundamental physics and many promising applications such as light emitters, photodetectors/sensors, valleytronics, and flexible nanoelectronics, due to its fascinating optical, electronic, and mechanical properties. Herein, basic exciton properties of monolayer WS2 are reviewed including neutral excitons, charged excitons, bounded excitons, biexcitons, and the effects of electrostatic gating, chemical doping, strain, magnetic field, circular polarized light, and substrate on these excitonic structures. Besides basic excitonic emission, single‐photon emission, exciton–polaritons, and stimulated emission in monolayer WS2 are also discussed. The understanding of these optical phenomena is critical for the development of potential optical applications in electronic and optoelectronic devices. Finally, a summary and future prospective of the challengers and developments regarding 2D semiconductor WS2 is presented.